Van Neck–Odelberg disease: A rare cause of pain in pediatric pelvis - Camacho, Daniel; Bernal, Patricia; Cifuentes, Luisa; Rivero, Oscar (World Journal of Nuclear Medicine, 2020)
Van Neck-Odelberg disease or ischiopubic osteochondritis, is a rare cause of pain in the pediatric pelvis due to late closure in synchondrosis ischiopubic, whose main symptom is an asymmetric pain that can cause a limitation in movement or limp. The different characteristics by images from simple radiography, computed tomography, MRI and bone scintigraphy scan will increase certainty diagnosis and will allow the correct differential diagnosis with fractures, posttraumatic osteolysis, infections or tumors, that leads to unnecessary invasive procedures, this being a benign disease with an evolution and improvement that occurs in weeks or months with conservative treatment. A case of a 15-year-old boy who consulted our hospital with an extra-institutional diagnosis of right ischiopubic fracture. After being evaluated by different imaging methods, a diagnosis of Van Neck-Odelberg or ischiopubic osteochondritis was made.
Keywords: Hip pain; inguinal pain; ischiopubic synchondrosis; osteochondritis; Van Neck–Odelberg